A developer's guide to the semantic web - Liang, Yu (Heidelberg, Netherlands : Springer, 2011)
Covering the theory, technical components and applications of the Semantic Web, this book's unrivalled coverage includes the latest on W3C standards such as OWL 2, and discusses new projects such as DBpedia. It also shows how to put theory into practice
1. A web of data: toward the idea of the semantic web -- 2. The building block for the semantic web: RDF -- 3. Other RDF-related technologies: microformats, RDFa, and GRDDL -- 4. RDFS and ontology -- 5. OWL: web ontology language -- 6. SPARQL: querying the semantic web -- 7. FOAF: friend of a friend -- 8. Semantic markup at work: rich snippets and searchmonkey -- 9. Semantic wiki -- 10. DBpedia -- 11. Linked open data -- 12. Building the foundation for development on the semantic web -- 13. Jena: a framework on the semantic web -- 14. Rose your nose: a basic semantic web agent -- 15. More application examples on the semantic web
Includes index
Keywords: Information storage and retrieval systems; Library science; Semantic Web; Web site development